Risk stratification for cervical precancer and cancer by DH3‐HPV partial genotyping and cytology in women attending cervical screening: A retrospective cohort study. Issue 2 (13th January 2023) - Fu, Yunfeng; Li, Ying; Li, Xiao; Wang, Xinyu; Lü, Weiguo
Abstract: To evaluate the effect of DH3‐human papillomavirus (HPV) partial genotyping for risk stratification in cervical cancer screening, we conducted a post hoc analysis within a retrospective cohort of 7263 Chinese women aged 21–71 years who participated in population‐based screening. The residual cytological samples at baseline were retested with DH3‐HPV and Hybrid Capture 2 (HC2) assay after 3‐year follow‐up. Risk values with 95% confidence intervals (CIs) of cervical intraepithelial neoplasia (CIN) grade 3/2 or worse (CIN3+/CIN2+) were estimated based on HPV and cytology results. The report complies with the STROBE statement. Across every cytological result, risk estimates obtained from DH3‐HPV and HC2 were similar or almost identical. By DH3‐HPV partial genotyping, risks of CIN3+/CIN2+ were invariably higher for HPV16/18 than other high‐risk HPV (hrHPV). Among women with normal cytology, immediate CIN3+ risks were 8.16% (95% CI = 4.19%–15.28%) for HPV16/18 positive and 0.48% (95% CI = 0.13%–1.73%) for other hrHPV positive. Among women with any abnormal cytology, immediate CIN3+ risks were 33.33% (95% CI = 22.24%–46.64%) for HPV16/18, and 13.33% (95% CI = 8.37%–20.56%) for other hrHPV. Among 5840 women completed 3‐year follow‐up, the cumulative CIN3+ risk was 25.56% (95% CI = 18.91%–33.59%) for HPV16/18 and 8.22% (95% CI = 6.02%–11.13%) for other hrHPV. Women with an HPV‐negative result with DH3‐HPV or HC2 test had very low cumulative 3‐year CIN3+ risk (0.06%, 95% CI = 0.02%–0.17%), which was about one‐tenth of women with normal cytology at baseline (0.62%, 95% CI = 0.45%–0.86%). Similar patterns were observed for the endpoint of CIN2+. These findings suggest that partial genotyping of DH3‐HPV performs well in risk stratification, which can better balance the benefits and harms of cervical cancer screening.